A Study of Needle Stick Injuries among Nursing College Students in a Tertiary Care Hospital in Chengalpattu District, Tamil Nadu - Ramya M R; Geetha M; Jawahar S S (Indian Association of Preventive and Social Medicine, 2021)
Introduction: Needle stick injuries (NSIs) are the most potential occupational hazards among nursing personnel with possible transmission of blood borne pathogens. As nursing students are in the learning stage, they might be at higher risk of acquiring the injuries.Objectives: Todetermine the prevalence of needle stick injuries and to assess the awareness, attitude and practices followed with regard to NSIs.Methodology: An online cross-sectional study was conducted from October to December 2020 among 175 students in a nursing college in Chengalpattu district Tamil Nadu, using a pretested semi- structured questionnaire, adopting universal sampling technique. Data was analyzed using SPSS version 23. Categorical variables were summarized as Percentages and chi square test was used for statistical analysis. Results: The overall prevalence of needle stick injury among nursing college students was 16%.Final year studentsweremore exposed to the injuries(35.7%). Majority (96.57%) of the students were aware about universal precaution guidelines, 57% of students were aware about the diseases transmitted by NSI, 97.71% were aware about safety devices and 67.43% of students were aware about the post-exposure prophylaxis in management of NSIs.Among the students, 71.43% had used gloves regularly, 72% were immunized against Hepatitis B, only 25.71% of students attended Integrated Counselling Testing Centre(ICTC) and more than half of the students always practiced recapping needle after giving injections. Conclusion: Majority of the students in this study were aware about NSIs, their attitude towards NSIs was agreeable. The practices reported though assessed through online survey was found to be deficient.Periodic education and training need to be done to avoid injuries in future.